Textbook versions of Noli Me Tangere's first chapter: How changes to the text affects its meaning and the attainment of desired learning competencies - Santos-Syjueco, Marilou (Animo Repository, 2005)
The study determines how the first chapter of the Noli Me Tangere is interpreted in textbook versions. Specifically, to show the changes made by textbook versions to the original text of Una Reunion; to analyze how these changes affect the intended meaning of the original text; to discuss how these changes affect the attainment of the desired learning outcomes stipulated by the Department of Education for the study of the novel. The study makes use of Una Reunion, the first chapter of the Noli Me Tangere as interpreted in 11 textbook versions of the novel. The versions were published between 1998 and 2004. The study is limited to comparing the textbook versions with the Spanish original to pinpoint changes made in the text. Because of limited working knowledge of Spanish, the translation of Patricio Mariano, which was published by the JRNCC in 1961, is used as anchor.The desired learning competencies (DLCs) used are the ones listed in the Paatnubay sa Operasyonalisyon ng Filipino sa Batayang Edukasyon sa Level Sekondari for the study of Noli Me Tangere as circulated for implementationn by the Department of Education Bureau of Secondary Schools. The specific DLCs used are the ones listed under the Unang Markahan (First Grading Period) and Ikalawang Markahan (Second Grading Period) during which the first chapter of the novel is taken up. The first chapter of Noli Me Tangere is divided into sentences, the sentences into segments of thought phrases. There are 181 sentences in all. The sentences of the versions are divided accordingly and tabulated alongside the original text. There are usually 12 columns to a table. In some instances, when versions do not have interpretations of a particular sentence, they are deleted or not anymore represented in the tables. There are a total of 181 tables.The presentation of tables and the listing of changes made to each sentence by the versions that come after each table answer problems one and two. The changes are any of the following: a. deletions, either completely or partially of otherwise meaningful sentences of apothegms, phrases or words; b. paraphrase or rewording of the original text in such a way that the meaning is either twisted or the writing loses any semblance to the original text; c. summaries of sentences particularly dialogues between characters into what the version author thinks is the message conveyed by the original; d. replacement or modernizing of information with something deemed more comprehensive to target readers; e. "explicitations" ar addition of information when a concept is deemed not clear to target readers.A second part discusses how the changes made by the versions might affect the attainment of desired learning competencies (DLCs) prescribed by the Department of Education for the study of the Noli in the third year high school. The description of the setting and the introduction of the characters are affected by the changes that mostof the versions undertake1. deletions are common in most versions, which explains why their first chapters are noticeable shorter than the original; 2. in several versions meaningful segments are also deleted if not shortened which lessened their impact; 4. paragraphs are freely summarized and in the process the literariness of such are diminished; 5. paragraphs as well as spoken line are merely reported or paraphrased and this too lessen the drama and characterization that they are intended to carry; 6. in several versions, "explicitations" or additional information are freely inserted within text, which gives the false impression that they also appear in the original Rizal's connection to his present-day readers may be waning and the not so faithful versions of his works contribute a lot to this problem. Some versions are so far removed from the original that the readers of today are virutally reading another person's thoughts and not anymore of Rizal's. The desired learning competencies prescribed by the Department of Education may not be fully attained in view of the changes the original text of Una Reunion undergoes in most versions.